One-stop assembly of adherent 3D retinal organoids from hiPSCs based on 3D-printed derived PDMS microwell platform. (1st July 2023) - Sun, Xihao; Cui, Zekai; Liang, Yuqin; Duan, Chunwen; Chan, Hon Fai; Mao, Shengru; Gu, Jianing; Ding, Chengcheng; Yang, Xu; Wang, Qing; Tang, Shibo; Chen, Jiansu
Abstract: The three-dimensional (3D) retinal organoids (ROs) derived from human induced pluripotent stem cells (hiPSCs), mimicking the growth and development of the human retina, is a promising model for investigating inherited retinal diseases in vitro . However, the efficient generation of homogenous ROs remains a challenge. Here we introduce a novel polydimethylsiloxane (PDMS) microwell platform containing 62 V-bottom micro-cavities for the ROs differentiation from hiPSCs. The uniform adherent 3D ROs could spontaneously form using neural retina (NR) induction. Our results showed that the complex of NR (expressing VSX2), ciliary margin (CM) (expressing RDH10), and retinal pigment epithelium (RPE) (expressing ZO-1, MITF, and RPE65) developed in the PDMS microwell after the differentiation. It is important to note that ROs in PDMS microwell platforms not only enable one-stop assembly but also maintain homogeneity and mature differentiation over a period of more than 25 weeks without the use of BMP4 and Matrigel. Retinal ganglion cells (expressing BRN3a), amacrine cells (expressing AP2a), horizontal cells (expressing PROX1 and AP2 α ), photoreceptor cells for cone (expressing S-opsin and L/M-opsin) and rod (expressing Rod opsin), bipolar cells (expressing VSX2 and PKC α ), and Müller glial cells (expressing GS and Sox9) gradually emerged. Furthermore, we replaced fetal bovine serum with human platelet lysate and established a xeno-free culture workflow that facilitates clinical application. Thus, our PDMS microwell platform for one-stop assembly and long-term culture of ROs using a xeno-free workflow is favorable for retinal disease modeling, drug screening, and manufacturing ROs for clinical translation.